2012
DOI: 10.1016/j.jcgg.2012.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Interventions targeting geriatric frailty: A systemic review

Abstract: a b s t r a c tGeriatric frailty has drawn growing interest in recent years for its associations with multiple adverse outcomes. Previous studies showed that interventions may improve some aspects of frailty such as physical function. However, interventions targeting the entire frailty construct have not been systemically reviewed. We conducted a comprehensive search for randomized controlled trials targeting geriatric frailty. Only trials that measured outcomes based on their predefined frailty indicators wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 35 publications
(61 reference statements)
0
42
0
2
Order By: Relevance
“…For frailty as an interventional target, the small number of uses estimated in our study aligns with other research. A recent systematic review found only 11 interventional studies with frailty as an outcome (Lee et al, 2012); among these studies, 4 used the PFP (or a modified version) and 7 used less common frailty indicators. Also, two recent interventional studies measured frailty outcomes using the PFP (Fairhall et al, 2015; Cesari et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…For frailty as an interventional target, the small number of uses estimated in our study aligns with other research. A recent systematic review found only 11 interventional studies with frailty as an outcome (Lee et al, 2012); among these studies, 4 used the PFP (or a modified version) and 7 used less common frailty indicators. Also, two recent interventional studies measured frailty outcomes using the PFP (Fairhall et al, 2015; Cesari et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…Also, studies combining more than two domains were not in their scope of interest 23. Other reviews focused on other populations (eg, sarcopenia or obesity)22,2426 or included studies that used no diagnostic tool to determine the frail population27,28 or used poor search criteria for (pre) frail participants (eg, only one keyword in database search) 29. Because of the limitations of existing reviews as well as to include information from recent studies, a systematic review was conducted, aiming to provide an overview of the effects of controlled multi-domain interventions in (pre)frail people aged ≥65 years on frailty status and score, cognition, muscle mass strength and power, and functional and social outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Research to develop interventions targeting frailty is nascent [18, 19]. Key outcomes of interest have been quality of life, functional status (e.g., ability to perform activities of daily living), depression, and physical function.…”
Section: Introductionmentioning
confidence: 99%